Mudbrick Settlements of the Oman Peninsula Inhabited - Abandoned - Re(dis)covered - Döpper, Stephanie; Mershen, Birgit; Kanditt, Josephine; Biezeveld, Irini; Schmidt-Lux, Thomas (Sidestone Press, 2025)
Caught between the poles of remembering and forgetting, glorification and neglect, the abandoned mudbrick settlements (ḥārāt) of Oman are a vital object of conflicting processes of interpretation and negotiation. Adopting a diachronic perspective, the multi-disciplinary book’s chapters examine their past, present and future. The book presents approaches and results of archaeological, ethnographic, historical and sociological research on abandoned ḥārāt. Oman’s landscape is dotted with abandoned mudbrick settlements and quarters, known as ḥārāt, either isolated in the countryside or surrounded by vibrant, modern urban centres. Most of them were abandoned during the economic upturn and opening of the country after Sultan Qaboos bin Said came to power in 1970. People’s move from traditional mudbrick to modern concrete houses led to the deterioration and decay of the physical substance of the mudbrick buildings. In the face of these conditions, various Omani and international actors have repeatedly warned against the uncontrolled loss of this valuable cultural heritage. The former inhabitants of the mudbrick houses and their descendants have also repeatedly emphasised their emotional attachment to these abandoned places and their personal significance to them. At the same time, others, especially tourists, have glorified the dilapidated state of the ruins as an aesthetically beautiful backdrop for a romanticised vision of the past. This was the starting point for the interdisciplinary research project “The abandoned mudbrick settlements of central Oman: Between romanticisation and neglect”, funded by the Gerda Henkel Foundation as part of the “Lost Cities” programme between 2020 and 2022, and conducted by the editors of the present volume. It constitutes the proceedings of the closing conference of the project, in which team members present their results and leading experts give their input on inhabited, abandoned and re(dis)covered mudbrick settlements in the Sultanate of Oman.
Keywords: Architecture – Oman; Archéologie – Oman; Urbanisme – Oman